STUDY THE PROTECTIVE AND THERAPEUTIC EFFECTS OF CRUDE GARLIC ON MORTALITY, OOCYST OUTPUT AND HEPATIC LESIONS IN EXPERIMENTAL INFECTION WITH EIMERIA STIEDAE IN DOMESTIC RABBITS - Houida H. Abed Alia Y. Yakoob (Basrah Journal of Veterinary Research)
A study was conducted to investigate the protective and therapeutic effects of crude garlic (Allium sativum) against experimental infection with Eimeria stiedae in rabbits. Forty- two rabbits Divided into four groups : six rabbits a healthy control group (HC); 12 rabbits as challenged –garlic –protected group (CGP) which received a daily dose of 0.5 gkg body weight crude garlic for five days before challenged with E. stiedae ;12 rabbits as challenged –garlic –treated group (CGT) which received a daily dose of 0.5 gkg body weight crude garlic for five days after challenged with of E .stiedae and 12 rabbits as infected group (IG).The challenge dose was 4×104 sporulated E. stiedae oocyst per rabbits .Mortality rate , fecal oocyst count were elevated throughout the experiment. At the end of the experiment ,all rabbits were killed and histopathological examination was performed. Mortalities were recorded in HC group , while mortality was found to be 8% ,25% and 50% in the CGP ,CGT and IC groups, respectively. CGP rabbits have the lower numbers of oocysts than those in the CGT than those in IC groups. Hepatic lesion were less severe in the CGP and CGT groups than in IC group. The results showed that oral administration of crud garlic ameliorated the adverse impacts of hepatic coccidiosis on rabbits as prophylactic and therapeutic , but garlic was more effective as prophylactic .